Unveiling the Factors Impacting Student Study Completion: Insights from the Simple Multi-Attribute Rating Technique Exploiting Rank Method - Hariyati, Nunuk; Setyowati, Sri; Amalia, Kaniati; Islamiah, Nia (Jurnal Pedagogi dan Pembelajaran, 2024)
This study is motivated by the prevalent issue of a high number of postgraduate students in higher education struggling to complete their studies on time. This phenomenon not only impacts individual students but also affects the overall efficiency of institutional management in higher education. The study aims to analyze the factors influencing study completion. Employing a quantitative approach, this research applies the SMARTER (Simple Multi-Attribute Rating Technique Exploiting Rank) method. Internal factors, including competence, learning motivation, intelligence, attitude, and aptitude, as well as external factors such as family support and institutional services, were assessed through questionnaire data and weighted using the Rank Order Centroid (ROC) technique. The findings reveal that attitude (particularly the initiative for independent learning) is the most influential internal factor, while institutional factors such as coursework services and thesis supervision significantly impact study completion rates. The study concludes that strengthening personal attributes, such as the initiative for self-directed learning, and enhancing institutional support systems, including effective supervisory services, are critical in reducing study duration. These findings provide practical contributions for designing strategic interventions to improve student success and optimize academic program management in higher education.